A new species of Leiopathes (Anthozoa: Antipatharia) from the Great Meteor seamount (North Atlantic) - Molodtsova, Tina N. (Zootaxa, 2011)
Leiopathes montana, a new species previously reported as L. glaberrima (Esper), is described from the plateau of the Great Meteor seamount (North Atlantic) at depth 300–335 m. The new species can be easily distinguished from all other species of the genus by very thin at tips, slightly bended terminal branchlets 0.15–0.2 mm in diameter above the base, rather long in comparison to the size of the colony, small compressed triangular spines 0.02–0.03 mm long and 0.22–0.5 mm apart, and small densely-set polyps (6–9 per centimeter). Eight species assigned to the genus Leiopathes represent two distinct groups: (1) sparsely branched forms with longer terminal branchlets (L. glaberrima, L. valdiviae, L. acanthophora, L. bullosa, L. montana), and (2) forms with sinusoidal stem and branches, and very short branchlets forming flabellate fronds (L. expansa, L. grimaldii, L. secunda). The largest in size syntype of L. grimaldii Roule, 1902 collected off the Azores is proposed here as the lectotype, since it is the only full grown and complete specimen and also the only specimen illustrated and described in detail by Roule.